Carcass yield of cross-bred native chicken with fed dietary contain prebiotic from dahlia (Dahlia variabilis) and probiotic - Zakaria Husein Abdurrahman; Yoyok Budi Pramono; Nyoman Suthama (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
The use of probiotics and prebiotics together produces more beneficial effect to the microflora ecosystem in the intestine of chicken. The primary objective was to determine the carcass yield of the cross-bred native chicken fed diet containing dahlia (Dahlia variabilis) tuber powder as a resource of inulin combined with Lactobacillus sp. Animals used in this study were 168 birds of 21 days old cross-bred native chickens randomly allocated into six treatments with four replications. Data were analyzed as a completely randomized design in a 2×3 factorial of 2 levels of prebiotics and three levels of probiotics as the main effects. The treatments were 0.8% of dahlia tuber powder without Lactobacillus sp. (E1O0); 0.8% dahlia tuber powder combined with 1.2 mL of Lactobacillus sp. (108 CFU/mL) (E1O1); 0.8% dahlia tuber powder combined with 2.4 mL of Lactobacillus sp. (108 CFU/mL) (E1O2); 1.2% dahlia tuber powder without Lactobacillus sp. (E2O0); 1.2% dahlia tuber powder combined with 1.2 mL of Lactobacillus sp. (108 CFU/mL) (E2O1); 1.2% dahlia tuber powder combined with 2.4 mL of Lactobacillus sp. (108 CFU/mL) (E2O2). The feeding of dahlia tuber powder combined with Lactobacillus sp. showed no significant effect (P0.01) on the percentage of carcass weight, meat-bone ratio, and percentage of carcass cut weight on cross-bred native chicken. In conclusion, a feeding diet containing inulin derived from dahlia tuber combined with Lactobacillus sp. was not affected on carcass yield of cross-bred native chicken, although in previous studies, the same treatment could improve the meat quality of cross-bred native chicken